Product abundance, product delivery and price of product as determinants of online business profit performance / Syaza Fahzlin Mohd Fahrughazi and Amrizah Kamaluddin - Mohd Fahrughazi, Syaza Fahzlin; Kamaluddin, Amrizah (Universiti Teknologi MARA, 2021)
With the increasing number of small and medium enterprises (SMEs) in Malaysia, most young entrepreneurs have started to use the internet as their business platform. However, the issue faced by these SMEs is maintaining their profit performance and long-term business sustainability. In maintaining their profit performance, entrepreneurs need to ensure they have product abundance, provide the best service delivery and offer the best price in the market. Hence, the objective of this research was to examine the relationship between an online business performance with the three main pillars of online business - product abundance, product delivery and product price. 210 registered SMEs located in the Klang Valley were chosen as the survey respondents. The result indicates that, product abundance and product price have a significant relationship with the performance, while product delivery had no significant relationship. This study proved that price of products offered by online business is crucial in maintaining customers’ satisfaction that is closely related to sales and performance. The findings of the study assists the entrepreneurs in developing their business while contributing to the nation’s economy when more potential SMEs’ businesses with an online capability are able to penetrate into the international market and compete globally.